The Impact of Capital Structure on Financial Performance of Commercial Banks in Ethiopia (Global Journal of Management and Business Research, 2016)
Capital structure decisions are among the most important and crucial decisions for any business because of their effect on the performance of firms. The purpose of this paper was to investigate the impact of capital structure on financial performance of selected commercial banks in Ethiopia over the past five (5) year period from 2011 to 2015 using secondary data collected from financial statements of the commercial banks. Data was then analyzed on quantitative approach using multiple regression models. The study used two accounting-based measures of financial performance (i.e. return on equity (ROE) and return on assets (ROA)) as dependent variable and five capital structure measures (including debt ratio, debt to equity ratio, loan to deposit, bank's size and asset tangibility) as independent variable. The results indicate that financial performance, which is measured by both ROA, is significantly and negatively associated with capital structure proxies such as DER, SIZE and TANG whereas DR have negative impact.
Keywords: capital structure; financial performance; commercial banks